Usury Crimes in Post-Crisis China: The Underlying Economics and Beyond. Issue 4 (2nd October 2021) - Li, Dongmei; Peng, Zhe; Xiong, Kainan
Abstract: Although China's financial market grows more mature, an old, and arguably unethical form of finance—usury—still exists. In an age when the internet is widely available, various online lending platforms allow access to varieties of usury cloaked in new forms. In this article, we discuss three types of illegal usury crimes: campus loans that trick college students into heavy debts, naked loans that target young female students and use nude photos as collateral, and recipe loans that swindle people with valuable property (e.g., real estate). We found that these new forms of usury can be ascribed to a mismatch: the borrowers have a high marginal propensity to consume but limited liquidity to spend. Cultural, social, and legal factors in China are also significant contributors to the existence of these crimes.